The Effect of Extra Virgin Olive Oil (EVOO) on Expression of Vascular Endhothelial Growth Factor (VEGF) and Arteriole Number on Endometrium of Female Rattus norvegicus of Wistar Strain Exposed to Rhodamin B - Anisak, Siti; Sujuti, Hidayat; Sutrisno, Sutrisno; Mintaroem, Karyono; Nurseta, Tatit; Kalsum, Umi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
.